Feasibility and safety of the second-generation, frequency domain optical coherence tomography (FD-OCT): a multicenter study - Yoon, Joo Heung; Di Vito, Luca; Moses, Jeffrey W; Fearon, William F; Yeung, Alan C; Zhang, Shaosong; Bezerra, Hiram G; Costa, Marco A; Jang, Ik-Kyung (The Journal of invasive cardiology, 2012)
This study sought to assess the effectiveness and safety of the second-generation frequency-domain optical coherence tomography (FD-OCT) system. The second-generation FD-OCT was recently developed, with simplified imaging technique and faster acquisition time compared to the first-generation time-domain OCT. However, the safety and effectiveness of the FD-OCT has not been evaluated, and this study was conceived as a preapproval study for Food and Drug Administration clearance for clinical use in the United States. A total of 50 patients were enrolled from 3 institutions. Following stent implantation, the FD-OCT was performed with contrast injection through the guiding catheter to acquire pullback images with the pressure-triggered automatic pullback device. The primary endpoint was to achieve a median clear image length of more than 24 mm. Serious procedure-related or postprocedural adverse events (death, myocardial infarction, or ventricular arrhythmia) were recorded to assess safety of the device. The primary endpoint of obtaining >24 mm of median clear image length (CIL) was achieved in 94% of the subjects (47 out of 50), with measured CIL of 43.2 mm. In 5 patients (10.6%), a second attempt was necessary due to suboptimal image quality of the first pullback. In 36 patients (76.6%), a full stent length was obtained during the first attempt. There were no serious procedure-related or postprocedural adverse events. The new second-generation FD-OCT system provides fast and reliable resolution images of the coronary artery. The pullback can be safely performed over long segments of the artery without serious adverse events.